Physiological and social aspects associated with chromosomal abnormalities and congenital malformations in pregnancies perimenopausal - Haysha Maylla Castelo e Silva, Kelly Nunes de Almeida, Márcia Benvindo Braga, Elenir de Araújo Lago, Laiz Tavares Silva Pessoa, Itaiara Pereira da Silva (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i1.2093